Moderate-to-Severe Iodine Deficiency in the "First 1000 Days" Causes More Thyroid Hypofunction in Infants Than in Pregnant or Lactating Women. Issue 4 (15th February 2017) - Stinca, Sara; Andersson, Maria; Herter-Aeberli, Isabelle; Chabaa, Laila; Cherkaoui, Mohamed; El Ansari, Nawal; Aboussad, Abdelmounaim; Weibel, Sandra; Zimmermann, Michael B
Abstract: Background: Iodine deficiency early in the life cycle—the "first 1000 days"—can cause hypothyroidism and irreversibly impair neuromotor development. However, the relative vulnerability among women and infants during this critical period is unclear, making it difficult for country-based programs with limited resources to prioritize their iodine interventions. Objective: Our aim was to determine the prevalence of thyroid hypofunction in women and infants living in an area of moderate-to-severe iodine deficiency. Methods: In a cross-sectional survey in Morocco, we measured urinary iodine concentrations (UICs) and concentrations of thyroid-stimulating hormone (TSH) and total or free thyroxine (TT4 or fT4, respectively) in women of reproductive age ( n = 156), pregnant women ( n = 245), and lactating women ( n = 239) and their young infants ( n = 239). We calculated daily iodine intakes and measured iodine concentrations in breast milk and household salt. We compared the incidence of hypothyroidism between the 3 groups of women and with the infants. Results: Women of reproductive age, pregnant women, and lactating women had median (IQR) UICs of 41 (29–63), 32 (17–58), and 35 (19–62) μg/L; and estimated iodine intakes were ∼60%, 22%, and 26% of Recommended Nutrient Intakes (RNIs). The infants' median UIC was 73 (28–157) μg/L, which was greater than for all 3 groups of women ( P < 0.001), and their dietary intakes were 27% of the RNI. The prevalence of hypothyroidism was not significantly different between the 4 groups, whereas the prevalence of hypothyroxinemia was higher in infants (40%) than in the 3 groups of women (11–14%) ( P < 0.001). The median breast-milk iodine concentration was 42 (26–81) μg/L. Only 6% of salt samples were adequately iodized to a concentration of ≥15 ppm; 54% were inadequately iodized and 40% contained no measurable iodine. Conclusions: In an area of moderate-to-severe iodine deficiency, the prevalence of thyroid hypofunction is ∼4-fold higher in young infants compared with the 3 groups of women, suggesting that, in the "first 1000 days, " infants are more vulnerable than their mothers and that programs should prioritize iodine prophylaxis for this group.